2021
DOI: 10.1001/jamahealthforum.2021.4082
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Justice and Implications for US Health Care

Abstract: The recognition that where people live matters to their health has deep roots, highlighted in the works of Hippocrates, W. E. B. Du Bois, and in contemporary research on environmental and placebased factors that shape health. 1,2 Although health systems have come to accept their role in helping change community conditions in support of health, their complex institutional, financial, and sociopolitical considerations can prevent positive change or lead to more harm. We suggest that the concept of spatial justic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…But until we do all of these things and health systems consider their environment while holding themselves accountable to their communities, and advocate for change-we will continue to see studies like this one that suggest we need to improve our methods of caring for our patients. 10 The hyperacute, time-sensitive nature of acute ischemic stroke care means that patients are limited to what is offered to them. Accepting the status quo does not work when we are talking about access to the most effective disability-reducing intervention there is.…”
Section: The System Level and Larger Network Levelmentioning
confidence: 99%
“…But until we do all of these things and health systems consider their environment while holding themselves accountable to their communities, and advocate for change-we will continue to see studies like this one that suggest we need to improve our methods of caring for our patients. 10 The hyperacute, time-sensitive nature of acute ischemic stroke care means that patients are limited to what is offered to them. Accepting the status quo does not work when we are talking about access to the most effective disability-reducing intervention there is.…”
Section: The System Level and Larger Network Levelmentioning
confidence: 99%
“…As spatial justice is increasingly recognized as a critical component of building equitable systems of care, it will be important to examine the role of transfer patterns and the structure of the hospital network created by interhospital transfers in reinforcing or perpetuating disparities in patient access to high‐quality acute stroke care. 28 Strategies from network science may prove valuable. 29 , 30 …”
Section: Discussionmentioning
confidence: 99%
“…As spatial justice is increasingly recognized as a critical component of building equitable systems of care, it will be important to examine the role of transfer patterns and the structure of the hospital network created by interhospital transfers in reinforcing or perpetuating disparities in patient access to high-quality acute stroke care. 28 Strategies from network science may prove valuable. 29,30 Our findings also reinforce prior literature, as we found that stroke patients from racial or ethnic minority groups in California had lower odds than White patients of receiving reperfusion interventions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some authors suggest that the concept of spatial justice should necessarily be incorporated into the field of health to try to improve the health of the population (Baciu et al., 2021 ). Spatial justice is related to both the way territories face the pandemic and the typology and intensity of its effects on the population.…”
Section: Introductionmentioning
confidence: 99%